A case of ovarian juvenile granulosa cells tumor with peritoneal and jejunal localisation at Amath Dansokho Regional Hospital, Kedougou, Senegal - Wade, Mouhamadou; Diallo, Thierno A. T.; Tandian, Foulaké; Konate, Nankouma; Keita, Abdoulaye; Sarr, Alfred N.; Diop, Ousmane; Sane, Doudou; Faye, Khadim (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Granulosa tumors are rare ovarian tumors they belong to sex-cord and stromal tumor family. They are the most common type of malignant stromal tumor and have a good prognosis. There are two types: the adult type (AGCTs), which occurs most frequently between the ages of 40 and 70, and the juvenile type (JGCTs), which is uncommon. Juvenile granulosa tumors tend to involve a single ovary and occur mainly in people who are younger than 30 years. Metastatic spread is rare and, if present, is usually limited to the peritoneal cavity. We report a case of ovarian juvenile granulosa cell tumor extending to the jejunum and peritoneum in an 18-year-old female patient received in our institution.